Validating the Implementation Leadership Scale in Chinese nursing context: A cross‐sectional study. Issue 6 (7th May 2021) - Hu, Jiale; Gifford, Wendy; Ruan, Hong; Harrison, Denise; Li, Qingge; Ehrhart, Mark G.; Harrison, Mary‐Ann; Barrowman, Nick; Aarons, Gregory A.
Abstract: Aim: This study aimed to evaluate the validity, reliability and acceptability of the Implementation Leadership Scale in the Chinese nursing context. Design: This study utilized a cross‐sectional design. Methods: This study was conducted in one general tertiary hospital with 234 nurses (85.3% response rate) from 35 clinical units in China. Content validity, structural validity, convergent validity, reliability (internal consistency), agreement indices and acceptability were evaluated. The data collection was from December 1st, 2017 to June 30th, 2018. Results: Confirmatory factor analysis demonstrated a good model fit to the four‐factor implementation leadership model. The psychometric testing also indicated good convergent validity, high internal consistency and acceptable aggregation. Most participants completed the scale in two minutes or less and agreed or strongly agreed that the questions were relevant to implementation leadership, clear and easy to answer. Conclusions: This study demonstrated that the Chinese Implementation Leadership Scale is a valid, reliable and pragmatic tool for measuring strategic leadership for implementing evidence‐based practices.